First Improving the quality of education through the use of individual assignments in classroom mathematics lessons (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the concept of individuality, the types and tasks of individual assignments, and the importance of individual assignments in first grade math classes.